Rubicon in Metabolic Diseases and Ageing - Minami, Satoshi; Nakamura, Shuhei; Yoshimori, Tamotsu (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is a conserved cellular degradation system that maintains intracellular homeostasis. Cytoplasmic components are engulfed into double-membrane vesicles called autophagosomes, which fuse with lysosomes, resulting in the degradation of sequestered materials. Recently, a close association between autophagy and the pathogenesis of metabolic diseases and ageing has become apparent: autophagy is dysregulated during metabolic diseases and ageing; dysregulation of autophagy is intimately associated with the pathophysiology. Rubicon (Run domain Beclin-1 interacting and cysteine-rich containing protein) has been identified as a Beclin-1 associated protein. Notably, Rubicon is one of few negative regulators of autophagy whereas many autophagy related genes are positive regulators of autophagy. In this mini-review, we focus on the various roles of Rubicon in different organs in the settings of metabolic diseases and ageing, and discuss its potential role as a promising therapeutic target.